Model Citizen Jurnalism dalam Pembinaan Civic Dispotition Mahasiswa: Penelitian - I Made Darsana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to examine the effectiveness of applying the citizen journalism model in fostering students' civic disposition, both on campus and in the community. The research method used is a literature study involving an in-depth analysis of various academic sources related to citizen journalism and civic disposition. A descriptive qualitative approach was applied to explore and describe the relationship between the implementation of the citizen journalism model and the development of students' civic character. The analyzed sources include journal articles, books, research reports, and related publications that discuss aspects of civic participation, media literacy, and character education within the context of citizenship education. The findings of this study indicate that the citizen journalism model has a significant impact on shaping students' civic character. This model effectively instills the values of citizenship, which are not only understood theoretically but also experienced through direct interaction. Citizen journalism encourages active student participation in public issues, strengthens values of honesty and moral courage, improves media literacy and critical thinking, builds empathy and tolerance through direct interaction, and fosters awareness of social responsibility. This result confirms that the citizen journalism model can be an effective approach in civics education to produce active, critical, and ethical citizens.